Following targeted routine antenatal anti‐D prophylaxis, almost half of the pregnant women had undetectable anti‐D prophylaxis at delivery - Kirsten Sørensen; Helena Eriksson Stjern; Bente Anita Grande Karlsen; Geir Tomter; Inger Ystad; Ida Herud; Mette Silihagen Bævre; Abid Hussain Llohn; Çiğdem Akalın Akkök (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction In September 2016, a nationwide targeted routine antenatal anti‐D prophylaxis program was implemented in Norway. The prophylaxis (anti‐D immunoglobulin) aims to cover the whole third trimester and is administered in gestational week 28 to RhD‐negative women who carry RhD‐positive fetuses. However, in many women, antibody screening at delivery does not detect anti‐D immunoglobulin. The goal of this study was to investigate the presumable role of dose and timing of antenatal anti‐D immunoglobulin administration in non‐detectable prophylaxis at the time of delivery. Material and methods In this retrospective observational study, RhD‐negative pregnant women who gave birth at Oslo University Hospital and Akershus University Hospital between January 2017 and December 2019 were analyzed. Women who received antenatal anti‐D immunoglobulin (1500 IU at Oslo University Hospital and 1250 IU at Akershus University Hospital) when fetal RHD genotyping at gestational week 24 predicted an RhD‐positive fetus were included if an antibody screen at delivery was available. Data from the blood bank, maternity information systems, and electronic patient records were used. Results Analysis of the 984 RhD‐negative women at the two hospitals revealed that 45.4% had non‐detectable anti‐D at delivery. A significant difference between the two hospitals was observed: 40.5% at Oslo University Hospital (n = 509) and 50.7% at Akershus University Hospital (n = 475) (p = 0.001). The proportion with non‐detectable anti‐D increased to 56.0 and 75.3%, respectively (p = 0.008) in the group of women who gave birth 12 weeks after routine antenatal anti‐D prophylaxis. Significantly fewer women had detectable anti‐D at delivery when the lower anti‐D immunoglobulin dose (1250 IU) was administered antenatally. Multiple logistic regression indicated that the time interval between routine antenatal anti‐D prophylaxis and delivery, in addition to anti‐D dose, were significantly associated with detectable anti‐D at delivery (p < 0.001). Conclusions We do not know which RhD‐negative pregnant women, despite antenatal anti‐D prophylaxis, are at risk of RhD alloimmunization, when antibody screening is negative at delivery. Administration of antenatal prophylaxis should probably be moved closer to delivery, since the risk of fetomaternal hemorrhage is higher during the last weeks of the third trimester.